EVOLUSI KURIKULUM PENDIDIKAN DI INDONESIA DAN DAMPAKNYA TERHADAP KUALITAS PEMBELAJARAN DALAM DUA DEKADE TERAKHIR - Almira Ulimaz; Muthmainnah Mursidin; Busnawir (Berajah Journal, 2026)
Education in Indonesia has undergone significant curricular transformations over the past two decades, ranging from the 2004 Competency-Based Curriculum (KBK), the 2006 School-Based Curriculum (KTSP), the 2013 Curriculum, to the 2022 Merdeka Curriculum. This study aims to analyse the evolution of the education curriculum in Indonesia and its impact on the quality of learning from 2004 to 2024 using a literature review method with a descriptive qualitative approach. The research findings indicate that each curriculum change has introduced a new paradigm: shifting from teacher-centred to student-centred learning, from a focus on subject mastery to the development of competencies, and from national standardisation to flexibility and differentiation in learning. The positive impact of these changes is evident in the increased emphasis on critical thinking skills, creativity, collaboration, and character development through the Pancasila Student Profile. However, implementation faces significant challenges, including uneven teacher readiness, disparities in facilities between regions, an increased administrative burden on teachers, and instability in the education system due to overly frequent changes. Consequently, curriculum changes alone are insufficient to significantly improve the quality of education, as factors such as teacher quality and regional disparities have a greater influence on learning outcomes. This study concludes that the successful implementation of the curriculum requires holistic systemic improvements, including the continuous enhancement of teacher competencies, the equitable distribution of educational infrastructure and resources, and the support of a strong educational ecosystem.